2017
DOI: 10.3892/ol.2017.7486
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine inhibits cancer stem cell properties and regulates multiple malignant phenotypes in oral cancer

Abstract: Abstract. Piperlongumine (PL), a natural product ofPiper longum, inhibits multiple malignant phenotypes. Therefore, the present study examined whether PL suppresses cancer stemness in oral cancer. The cellular effects of PL were determined by examining alterations in tumor sphere formation, cell migration, invasion, proliferation ability, chemosensitivity and radiosensitivity. Reverse transcription-quantitative polymerase chain reaction analysis and western blotting were performed in order to determine molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 51 publications
2
14
0
Order By: Relevance
“… 19 Likewise, Chen et al have reported that the oral cancer cells after PL treatment were characterized by a decrease in the vimentin expression level. 18 In our study, the cells with lower level of PFN1 presented a strong reorganization of vimentin network and changes in the F-actin levels which were connected with alteration of PFN1 expression. In the case of cancer cells with a high degree of aggressiveness, the changes in morphology, cell adhesion, and the cytoskeletal proteins are very important in the context of cell migration.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“… 19 Likewise, Chen et al have reported that the oral cancer cells after PL treatment were characterized by a decrease in the vimentin expression level. 18 In our study, the cells with lower level of PFN1 presented a strong reorganization of vimentin network and changes in the F-actin levels which were connected with alteration of PFN1 expression. In the case of cancer cells with a high degree of aggressiveness, the changes in morphology, cell adhesion, and the cytoskeletal proteins are very important in the context of cell migration.…”
Section: Discussionsupporting
confidence: 56%
“…Literature have reported that PL suppresses migration in a different type of cancer including oral cancer, bladder, glioma, and hepatocellular carcinomas. 18 , 1 , 65 , 66 Our results clearly showed that the downregulation of PFN1 expression in lung adenocarcinoma A549 cells inhibited their migration. Moreover, the treatment with PL enhanced this effect, what is confirmed by the fact that transfected cells without PL covered the scratch wound slower than untreated A549 cells with a naïve level of PFN1.…”
Section: Discussionsupporting
confidence: 53%
“…This indicates that piplartine plus auranofin is able to eliminate CRC‐SCs. Interestingly, piplartine also inhibited stemness properties in leukemia [ 223 ] and oral cancer [ 224 ] and had less effect on the viability of normal cells [ 213 , 214 ].…”
Section: Cell Signaling Pathwaysmentioning
confidence: 99%
“…Furthermore, Gagat et al reported that treatments with 2-µM and 4-µM PL in A549 cells caused changes in the actin cytoskeleton [68]. In turn, a reduction in the level of vimentin was observed in PL-treated oral cancer cells (CGHNC8) [69]. The combination of the alkaloids used in this study caused an enhancement in the reorganization of the vimentin, actin and microtubule networks, which is probably associated with an increase in the cytotoxic effects of the alkaloids, as well as changes at the level of A549 cell proliferation and death.…”
Section: Discussionmentioning
confidence: 99%